Study on resource allocations for sustainable competitive advantage - Takala, Josu; Shylina, Daryna; Forss, Teppo; Malmi, Johannes (Polish Association for Production Management, 2013)
Today’s concern and problem for most of the companies is the way of surviving and prospering in current and future periods of time in the marketplace. Sustainable competitive ability can be one of the ways of adaptation to the global business and rapid environment requirements. Operational competitiveness is not easy to be sustainably improved because of unpredictable environment situations, such as continuous increasing customer needs, global competitive environment, rapid and unpredictable changes in government policy, company crisis during significant changes etc. However, it is possible to make adaptive adjustments on operations strategy level in dynamic business environment and to become competitive enough compared to the competitors. The purpose of this paper is to define and assess sustainable competitive advantage and the direction of development in housing business. It can be analysed by two core factors, i.e. Sense and Respond (S&R) methodology, Analytical Hierarchical Process (AHP) as well as Sustainable competitive advantage (SCA) method. This study also focuses on applying S&R method in order to optimize operational competitiveness as well as defining the competitive priorities of the case company. The analysis results show the critical areas in different departments of the case company, which can help the managers to make quick decisions. In addition, they reveal that during the crisis the resource allocation is continuously changing and therefore the operation strategy of the case company is not well defined as well as competitive advantages are not enough sustainable.
Keywords: sustainable competitive advantage; competitive priorities; manufacturing strategy; housing business; sense and respond; analytical hierarchical process; case study; fi=Tuotantotalous|en=Industrial Management|